A Case Report of Fenestration Deformity of Extracranial Vertebral Artery and Literature Review - Cao, Mingjuan; Qiang, Qun; Liu, Jia; Zhang, Miaomiao (The Thoracic and Cardiovascular Surgeon Reports, 2025)
Vertebral artery fenestration (VAF) is a rare anatomical variation of the vertebral artery that may affect the safety of clinical surgeries and interventional treatments. Although ultrasound is widely used to assess neck vessels, its application in diagnosing VAF has not been extensively investigated.This article reports a case of an 82-year-old male patient who was diagnosed with VAF following a neck vessel ultrasound examination prompted by poor blood sugar control. The ultrasound revealed an abnormal course of the left vertebral artery, leading to the diagnosis of VAF.Ultrasound, with its noninvasive nature and real-time imaging capabilities, is a valuable initial screening tool for diagnosing VAF. Despite its limitations, its ability to identify vascular anomalies such as VAF highlights its critical role in early detection, potentially improving patient outcomes and guiding clinical decision-making.
Keywords: artery/arteries; ultrasound; carotid arteries